Pengaruh Penerapan Model Blended Learning terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Peserta Didik Kelas XI SMA Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Angelita Sihotang; Simion Harianja; Taripar Aripin Samosir; Hasudungan Simatupang; Lustani Samosir (LPPM Politeknik Pratama, 2023)
The purpose of this study is to determine the interest in learning Christian Religious Education and Ethics of students who are taught using the Blended Learning model is higher than that learned with conventional models in grade XI of SMA Negeri 1 Sipoholon Learning Year 2023/2024. This study used quantitative methods, a type of True-Experimental approach with a form of Posttest-Only Design. The population is the entire class XI of SMA Negeri 1 Sipoholon for the 2023/2024 Learning Year which amounts to 242 people. The sample was determined by purposive sampling technique with the condition that the experimental learning material was set in the class, namely class XI MIA2 students totaling 34 people as an experimental class and XI MIA1 totaling 34 people as a control class. The research instrument used the distribution of questionnaires as many as 35 items. The t test used is the Separated Variance t t test according to the analysis requirements test, which is n1=n2 and the variance of both sample groups is homogeneous. The results of hypothesis testing are obtained by tcount = 9.59 > table (α = 0.05; dk = n1+n2 = 66) = ttable 1.671 then H0 is rejected and H1 is accepted. This study concluded that the interest in learning Christian Religious Education and Ethics of students who were taught using the Blended Learning model was higher than that learned with the conventional learning model in class XI MIA1 SMA Negeri 1 Sipoholon Learning Year 2023/2024.